Developing Student Independence in the Society 5.0 Era: A Review of the Entrepreneurship-Based Hidden Curriculum - Suparjo Suparjo; Sutrimo Purnomo; Nurul Azizah (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2026)
This study aims to analyze the implementation of an entrepreneurship-based hidden curriculum in developing students' independence in the Society 5.0 era. This field research employs a qualitative approach, utilizing a case study method, in two Islamic boarding schools: the Sunan Gunungjati Ba'alawy Islamic Boarding School in Semarang and the Darussalam Islamic Boarding School in Purwokerto. Data were collected through observation, interviews, and documentation, and then analyzed descriptively and qualitatively. The results of the study indicate that the entrepreneurship-based hidden curriculum in both Islamic boarding schools is an effective instrument in instilling the values ​​of student independence. At the Sunan Gunungjati Ba'alawy Islamic Boarding School, the entrepreneurship program encompasses seed sales, cooperatives, fertilizer production, agriculture, agro-farms, and the Micro Waqf Agency, as well as the provision of necessities. Meanwhile, at the Darussalam Islamic Boarding School, it takes the form of a drinking water depot, a convenience store, a mini market, and a laundry. The implementation of the hidden curriculum shapes students' independence in economic, social, emotional, intellectual, and temporal aspects, while fostering a productive, adaptive, and entrepreneurial mindset in accordance with the demands of Society 5.0. This study confirms that Islamic boarding schools play a strategic role in developing a generation of independent, creative, and globally competitive students through entrepreneurship education based on Islamic values.